Ghrelin – A Pleiotropic Hormone Secreted from Endocrine X/A-Like Cells of the Stomach - Stengel, Andreas; Taché, Yvette (Frontiers in Neuroscience, 2012)
The gastric X/A-like endocrine cell receives growing attention due to its peptide products with ghrelin being the best characterized. This peptide hormone was identified a decade ago as a stimulator of food intake and to date remains the only known peripherally produced and centrally acting orexigenic hormone. In addition, subsequent studies identified numerous other functions of this peptide including the stimulation of gastrointestinal motility, the maintenance of energy homeostasis and an impact on reproduction. Moreover, ghrelin is also involved in the response to stress and assumed to play a role in coping functions and exert a modulatory action on immune pathways. Our knowledge on the regulation of ghrelin has markedly advanced during the past years by the identification of the ghrelin acylating enzyme, ghrelin-O-acyltransferase, and by the description of changes in expression, activation, and release under different metabolic as well as physically and psychically challenging conditions. However, our insight on regulatory processes of ghrelin at the cellular and subcellular levels is still very limited and warrants further investigation.